Assessment of the state of intracardiac hemodynamics and myocardial remodeling in women with gonarthritis, hypertension and overweight - A. Pidlubna (Kazimierz Wielki University, 2021)
Abstract. The problem of comorbidity is one of the most pressing problems of modern medicine. The presence of arterial hypertension and overweight in patients with gonarthritis is associated with an earlier development of target organ damage and subsequent cardiovascular accidents. In order to assess intracardiac hemodynamics and types of myocardial remodeling in women with gonarthritis, hypertension and overweight, depending on their combinations, from 2018 to2021, a prospective study of 198 patients of the rheumatology department of the «City Hospital № 10» (Zaporizhzhia) was carried out. According to the results of the study, it was found that the presence of comorbid pathology in the form of arterial hypertension and overweight in female patients with gonarthritis negatively affects the contractile function of the heart, which is confirmed by a decrease in the main indicators of systolic function of the left ventricle; the specified combination of diseases leads to the formation of prognostically unfavorable types of left ventricular remodeling.